Profiling Shoulder Strength in Competitive Surfers - James Furness; Ben Schram; Tim Cottman-Fields; Brendan Solia; Josh Secomb (MDPI AG, 2018)
The shoulder region has the highest incidence of acute injuries in the sport of surfing. Little is known about the strength profile at the shoulder in a surfing cohort. The primary aim of this study was to establish the reliability of a rotator cuff strength testing procedure for surfers with a secondary aim of providing a profile of internal and external rotation strength in a competitive surfing cohort. Shoulder internal rotation and external rotation isometric strength was measured using a hand-held dynamometer in 13 competitive surfers. Intra-class coefficient values ranged from 0.97 to 0.98 for intra-rater reliability and were lower for inter-rater reliability ranging from 0.80 to 0.91. Internal rotation strength was greater than external rotation strength bilaterally (dominant, p = 0.007, non-dominant, p < 0.001). No differences (p < 0.79) were found in internal rotation strength between the dominant and non-dominant arms. External rotation strength was weaker on the non-dominant arm compared with the dominant arm (p < 0.02). The non-dominant arm external rotation to internal rotation ratio (0.82 ± 0.15) was lower (p = 0.025) than the dominant arm (0.88 ± 0.14). The current procedure is reliable with the same clinician, and results indicate musculature asymmetry specific to the external rotators.